<< Chapter < Page Chapter >> Page >

Solve 2 x = 3 x + 1 .

x = ln 3 ln ( 2 3 )

Got questions? Get instant answers now!

Is there any way to solve 2 x = 3 x ?

Yes. The solution is 0.

Equations containing e

One common type of exponential equations are those with base e . This constant occurs again and again in nature, in mathematics, in science, in engineering, and in finance. When we have an equation with a base e on either side, we can use the natural logarithm    to solve it.

Given an equation of the form y = A e k t , solve for t .

  1. Divide both sides of the equation by A .
  2. Apply the natural logarithm of both sides of the equation.
  3. Divide both sides of the equation by k .

Solve an equation of the form y = Ae kt

Solve 100 = 20 e 2 t .

100 = 20 e 2 t 5 = e 2 t Divide by the coefficient of the power . ln 5 = 2 t Take ln of both sides . Use the fact that  ln ( x )  and  e x  are inverse functions . t = ln 5 2 Divide by the coefficient of  t .
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Solve 3 e 0.5 t = 11.

t = 2 ln ( 11 3 ) or ln ( 11 3 ) 2

Got questions? Get instant answers now!

Does every equation of the form y = A e k t have a solution?

No. There is a solution when k 0 , and when y and A are either both 0 or neither 0, and they have the same sign. An example of an equation with this form that has no solution is 2 = −3 e t .

Solving an equation that can be simplified to the form y = Ae kt

Solve 4 e 2 x + 5 = 12.

4 e 2 x + 5 = 12 4 e 2 x = 7 Combine like terms . e 2 x = 7 4 Divide by the coefficient of the power . 2 x = ln ( 7 4 ) Take ln of both sides . x = 1 2 ln ( 7 4 ) Solve for  x .
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Solve 3 + e 2 t = 7 e 2 t .

t = ln ( 1 2 ) = 1 2 ln ( 2 )

Got questions? Get instant answers now!

Extraneous solutions

Sometimes the methods used to solve an equation introduce an extraneous solution    , which is a solution that is correct algebraically but does not satisfy the conditions of the original equation. One such situation arises in solving when the logarithm is taken on both sides of the equation. In such cases, remember that the argument of the logarithm must be positive. If the number we are evaluating in a logarithm function is negative, there is no output.

Solving exponential functions in quadratic form

Solve e 2 x e x = 56.

e 2 x e x = 56 e 2 x e x 56 = 0 Get one side of the equation equal to zero . ( e x + 7 ) ( e x 8 ) = 0 Factor by the FOIL method . e x + 7 = 0  or  e x 8 = 0 If a product is zero, then one factor must be zero . e x = 7  or e x = 8 Isolate the exponentials . e x = 8 Reject the equation in which the power equals a negative number . x = ln 8 Solve the equation in which the power equals a positive number .
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Solve e 2 x = e x + 2.

x = ln 2

Got questions? Get instant answers now!

Does every logarithmic equation have a solution?

No. Keep in mind that we can only apply the logarithm to a positive number. Always check for extraneous solutions.

Using the definition of a logarithm to solve logarithmic equations

We have already seen that every logarithmic equation log b ( x ) = y is equivalent to the exponential equation b y = x . We can use this fact, along with the rules of logarithms, to solve logarithmic equations where the argument is an algebraic expression.

For example, consider the equation log 2 ( 2 ) + log 2 ( 3 x 5 ) = 3. To solve this equation, we can use rules of logarithms to rewrite the left side in compact form and then apply the definition of logs to solve for x :

Questions & Answers

the gradient function of a curve is 2x+4 and the curve passes through point (1,4) find the equation of the curve
Kc Reply
1+cos²A/cos²A=2cosec²A-1
Ramesh Reply
test for convergence the series 1+x/2+2!/9x3
success Reply
a man walks up 200 meters along a straight road whose inclination is 30 degree.How high above the starting level is he?
Lhorren Reply
100 meters
Kuldeep
Find that number sum and product of all the divisors of 360
jancy Reply
answer
Ajith
exponential series
Naveen
what is subgroup
Purshotam Reply
Prove that: (2cos&+1)(2cos&-1)(2cos2&-1)=2cos4&+1
Macmillan Reply
e power cos hyperbolic (x+iy)
Vinay Reply
10y
Michael
tan hyperbolic inverse (x+iy)=alpha +i bita
Payal Reply
prove that cos(π/6-a)*cos(π/3+b)-sin(π/6-a)*sin(π/3+b)=sin(a-b)
Tejas Reply
why {2kπ} union {kπ}={kπ}?
Huy Reply
why is {2kπ} union {kπ}={kπ}? when k belong to integer
Huy
if 9 sin theta + 40 cos theta = 41,prove that:41 cos theta = 41
Trilochan Reply
what is complex numbers
Ayushi Reply
Please you teach
Dua
Yes
ahmed
Thank you
Dua
give me treganamentry question
Anshuman Reply
Solve 2cos x + 3sin x = 0.5
shobana Reply
Practice Key Terms 1

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask